2019
DOI: 10.1002/jia2.25228
|View full text |Cite
|
Sign up to set email alerts
|

The influence of age‐associated comorbidities on responses to combination antiretroviral therapy in older people living with HIV

Abstract: Introduction Multiple comorbidities among HIV ‐positive individuals may increase the potential for polypharmacy causing drug‐to‐drug interactions and older individuals with comorbidities, particularly those with cognitive impairment, may have difficulty in adhering to complex medications. However, the effects of age‐associated comorbidities on the treatment outcomes of combination antiretroviral therapy ( cART ) are not well known. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
15
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 36 publications
6
15
1
Order By: Relevance
“…We found that paradoxically, having no comorbidities increases the risk of VNS and PV. Several studies have found no association or a similar association to our study [31][32][33]. This may be explained by more frequent interactions with healthcare for people with comorbidities, due to their chronic conditions, where they may be encouraged to seek HIV care [34,35].…”
Section: Discussionsupporting
confidence: 66%
“…We found that paradoxically, having no comorbidities increases the risk of VNS and PV. Several studies have found no association or a similar association to our study [31][32][33]. This may be explained by more frequent interactions with healthcare for people with comorbidities, due to their chronic conditions, where they may be encouraged to seek HIV care [34,35].…”
Section: Discussionsupporting
confidence: 66%
“…Older age was a higher risk of death, we report that the HR of death among HIV/AIDS patients older than 50 years was 3.37 times that of those under 40, patients with 40-50 years old was not show higher HR of death compared with those under 40. Some studies have reported that older HIV/AIDS patients had more comorbidities and be signi cantly associated with second-line ART failure [21]. Married status and education status were not associated with mortality in our study.…”
Section: Discussioncontrasting
confidence: 55%
“…In addition to the factors mentioned above, older age, male sex, lower nadir CD4 T‐cell counts, lower CD4/CD8 ratios, and a lower naïve/memory CD4 + T‐cell ratio have been associated with a blunted immunological response to ART treatment. Ethnic origin is also associated with immune recovery .…”
Section: Potential Mechanisms Of Incomplete Immune Reconstitutionmentioning
confidence: 99%